2014
DOI: 10.4049/jimmunol.1303401
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies Induced by Chimeric Cytokine-HIV Envelope Glycoprotein Immunogens

Abstract: Cytokines are often used as adjuvants to increase the immunogenicity of vaccines as they can improve the immune response and/or direct it into a desired direction. As an alternative to co-delivering antigens and cytokines separately they can be fused into a composite protein, with the advantage that both moieties act on the same immune cells. The HIV-1 envelope glycoprotein (Env) spike, located on the outside of virus particles and the only relevant protein for the induction of neutralizing antibodies (NAbs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 77 publications
0
12
1
Order By: Relevance
“…These rabbits were immunized with 30 g of Env-Fd protein in ISCOMATRIX TM adjuvant at weeks 0, 4, and 20. In previous vaccination experiments using similar protocols, five to six animals per group provided enough statistical power to detect significant differences between two groups in binding antibody measurements (35,37). Therefore, we used six New Zealand White rabbits for the experiments in Fig.…”
Section: Sds-page Bn-page and Westernmentioning
confidence: 99%
See 1 more Smart Citation
“…These rabbits were immunized with 30 g of Env-Fd protein in ISCOMATRIX TM adjuvant at weeks 0, 4, and 20. In previous vaccination experiments using similar protocols, five to six animals per group provided enough statistical power to detect significant differences between two groups in binding antibody measurements (35,37). Therefore, we used six New Zealand White rabbits for the experiments in Fig.…”
Section: Sds-page Bn-page and Westernmentioning
confidence: 99%
“…Therefore, we used six New Zealand White rabbits for the experiments in Fig. 5, A and B that were immunized in the abdominal dermis at week 0, 2, 4, 8 with 125 g endotoxin-free DNA encoding Env-IZ, Env-IZN4, HA-IZ, and Env-IZN4 using gene gun technology (35,37). All protocols dealing with animal manipulations were in accordance with guidelines published by FELASA (Federation of European Animal Science Association) and GV-SOLAS (German Society of Laboratory Animal Science) and were reviewed by the Harlan, MFD Diagnostics, or Davids Biotechnologie Animal Care Committees, as appropriate.…”
Section: Sds-page Bn-page and Westernmentioning
confidence: 99%
“…Here, we found that Env APRIL did not induce autoAbs targeting the APRIL domain in mice or rabbits and similar results were obtained with Env CD40L . These results were in stark contrast with the high anti-rGM-CSF and anti-rIL-21 responses observed in rabbits immunized with Env IL-21 and Env GM-CSF [20]. The anti-APRIL responses were>250-fold lower than those against GM-CSF and>25-fold lower than those against IL21, suggesting that the type of cytokine (trimeric TNF superfamily member vs. monomeric 4-helix bundle cytokine) influences the propensity to generate autoAbs.…”
Section: Discussionmentioning
confidence: 61%
“…We have previously reported on the strong induction of anti-cytokine responses with the chimeric proteins Env IL-21 and Env GM-CSF , which are similar in design to the Env APRIL described here [20]. Therefore, we looked for the presence of anti-APRIL Abs in sera from rabbits immunized with Env rAPRIL construct using a similar ELISA as we described previously for IL-21 and GM-CSF (see Materials and Methods and [20]).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation